Pemulihan Pembelajaran di Sekolah Melalui Kurikulum Prototipe - Syamsul Bahri (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
This study aims to describe a prototype curriculum that has similarities with the national curriculum since it is a simplified version. This type of research is a qualitative analysis with a literature study approach and literature study. Searching for in-depth documentation was carried out to obtain data. The discussion covers literature search, literature evaluation using a number of criteria, literature content review and analysis, also the synthesis of prototype curriculum literature content. The data analysis used a critical and accurate content analysis model consisting of three stages, namely collecting, reviewing documents, triangulating data, and confirming the validity of the data. The results show that the prototype curriculum was carried out through stages based on capacity and target setting by the education unit and it was necessary to analyze and develop the operational curriculum of the education unit with a focus on growing the Pancasila character for students, based on the seven selected themes. Following up on these findings, it is necessary to emphasize the voice of the students. Whatever changes occur, they must provide the maximum benefit to students.